(untitled) (Medico Legal Update, 2021)
A blood transfusion is a way of adding blood to your body after an illness or injury. It’s a kind of life saving procedure. But this procedure also has life threatening hazards. Transfusion transmitted infections are one of the major side effects of blood transfusion. We can prevent them by proper screening of blood products and public awareness. To know about trend of transfusion transmitted infections (TTI) for the blood donors of Dhiraj hospital blood bank, the study was done. Method: Study was done including blood donors of age 18-65 years from 2011 to 2016 retrospectively. TTIs testing for HIV, HBV and HCV was done with 3rd generation ELISA but from the year 2016 onwards 4th generation ELISA was used for HIV testing. Syphilis and malaria screening was done with rapid card test. Result: Over a six year period total blood donation was 20,392. The overall prevalence of HIV, HbsAg, HCV, syphilis and malaria were 0.16%, 1.43%, 0.10%, 0.61% and 0.009% respectively. Conclusion: Nucleic acid amplification testing (NAT) must be applied that identify positive blood donor during the immunological window period before seroconversion. Information to TTIs reactive donor is a best method to prevent the chance of repeated reactive donation.